Agroforestry Land Management with the Community of Candi Rejo Village, Biru-Biru District, Deli Serdang, North Sumatra - Delvian; Elfiati, Deni; Rambey, Ridahati (Talenta Publisher, 2019)
Community Service Program in agroforestry land management together with the people of Candi Rejo of Village, Biru- Biru Sub-District, Deli Serdang, North Sumatra, aims to assist the community in managing agroforestry land to improve community skills in managing their agroforestry land. Some of the activities carried out are making compost using cocoa waste and animal husbandry, prunning cocoa plants to reduce pest and disease attacks and planting mindi, avocado, durian species for enrichment of species on agroforestry land. Based on the result of interviews with farmers that the use of compost is more effective in increasing cocoa production.